Learning Through Music Workshops - Dečman, Adrijana (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter explores the benefits of learning through music workshops that are grounded in a participatory and creative approach. Music workshops foster creativity, collaboration, and student autonomy, supporting the development of musical skills, critical thinking, and socio-emotional competencies. Special attention is given to the structuring and planning of workshops, incorporating practical musical activities, and emphasizing the importance of assessment and feedback. Strategies are presented for integrating music into students' daily lives, thereby enhancing their creativity and motivation. Music workshops are shown to be an effective approach that transcends traditional music education, promoting holistic personal growth, student connectedness, and greater engagement in learning.